DETERMINAN TINGKAT STRES REMAJA PUTRI DENGAN KELUHAN KEPUTIHAN - Kas, Sri Rezkiani (LPPMK STIKES Widyagama Husada, 2023)
Vaginal discharge is a perennial problem for women. The effects of this vaginal discharge include infection, pelvic inflammatory disease, infertility, and even excessive anxiety and self-confidence. Excessive and uncontrollable anxiety causes stress. Based on previous research related to adolescent vaginal discharge, there are several factors that can cause an increase in vaginal discharge including knowledge, attitudes and behavior, and age at menarche, but coping with stress and the frequency of vaginal discharge is higher in Makassar city where there are more people with 388,070 women between the ages of 15 and 19 who have the potential to experience reproductive health problems, it is important to conduct research to improve the health of young women, especially among adolescent girls. This study aims to determine the relationship between female adolescent stress levels and complaints of vaginal discharge in female adolescents at Makassar State High School in 2022. The type of research used was cross sectional using a descriptive approach. Based on the results of the analysis showed there was a relationship vaginal discharge to stress (0.017), age at menarche (0.021) and personal hygiene (0.032). It is recommended to continuously improve knowledge through technological advances, such as using the internet to search for reproductive health information for adolescents, especially young women.